Great mysteries of the air - Barker, Ralph (Pan Books, 1968)
Amelia Earhrt - The Lady Be Good - The Atlantic Princess - The World of Albert Voss - Leslie Howard and the Party of Four - The long silence of Star Tiger - Ray Hinchliffe and Elsie Mackay - A Mistake on a Map - The Wrong Door - Glenn Miller - "Wrong-Way" Corrigan - The Duke of Kent - The Infernal Machine - Bill Lancaster.